Updated PSO optimised fuzzy‐PI controlled buck type multi‐phase inverter‐based PMSM drive with an over‐current protection scheme. Issue 12 (2nd September 2020) - Sain, Chiranjit; Banerjee, Atanu; Kumar Biswas, Pabitra; Sudhakar Babu, Thanikanti; Dragicevic, Tomislav
Abstract : This study confers a novel approach towards fuzzy‐PI (proportional–integral) controlled pulse width modulation (PWM) controlled permanent magnet synchronous motor (PMSM) drive operated through a conventional voltage source inverter (VSI) supplemented with buck‐converter fed current source inverter (CSI). It is observed that in a PWM controlled VSI, output voltage and current obtained contains certain harmonic distortion. A buck‐converter fed CSI is capable of minimising the voltage and current ripples prominently even with the application of PWM. Thereby, in this study, an economic, as well as robust design procedure for the buck converter, fed CSI is proposed. Moreover, a particle swarm optimisation (PSO) mechanism is introduced to optimise the performance of the proposed fuzzy logic controller. Additionally, an over‐current protection scheme of the PMSM motor is proposed. The performance of a PMSM drive is analysed in MATLAB/SIMULINK platform. Furthermore, the proposed concept is tested and verified in a real‐time test‐bench developed in the laboratory. Finally, from the performed test conditions, it can be confirmed that the proposed current control strategy of the drive system shows excellent performance in various operating conditions and can be employed in light‐weight electric vehicles.